Sanksi Pidana terhadap Anak di Bawah Umur yang Telah Melakukan Pencurian disertai Pembunuhan Seorang Gadis Pegawai Bank - Ni Made Ratna Pratiwi; Anak Agung Sagung Laksmi Dewi; I Made Minggu Widyantara (Fakultas Hukum, Universitas Warmadewa, 2022)
Criminal acts committed by minors are very worrying. Criminal acts committed by children are not only one type of crime, but also criminal acts such as theft accompanied by violence so that it takes a person's life. The purpose of this research is to analyze the factors that cause minors to commit the crime of theft with murder to find out criminal sanctions against minors who have committed the crime of theft accompanied by the murder of a bank employee girl. Using normative legal methods and approaches to legislation, facts, cases and analysis of legal concepts. This study uses qualitative analysis techniques. In this study there are three sources of material, namely primary data, secondary data and tertiary data. The primary legal materials are: the results of interviews with both informants and respondents, and the Law on the Juvenile Criminal Justice System. Sources of secondary legal materials in the form of data have properties as a complement to primary data such as: Legal journals, books, scientific works and materials on the internet as additional material. And the source of tertiary legal material is material that supports secondary material. The data collection technique is by observing, writing the observed results. The results show that the factors causing the perpetrators to commit the crime of theft accompanied by murder or theft with violence are: because the perpetrator has been known to be naughty since childhood, lack of education, comes from a broken home family, and economic factors . The crime of theft accompanied by violence resulting in the death of a person is sentenced to imprisonment for 7 (seven) years and 6 (six) months at the Child Correctional Institution in Karangasem